Antipsychotic treatment of very late-onset schizophrenia-like psychosis (ATLAS): a randomised, controlled, double-blind trial - Howard, Robert; Cort, Elizabeth; Bradley, Rosie; Harper, Emma; Kelly, Linda; Bentham, Peter; Ritchie, Craig; Reeves, Suzanne; Fawzi, Waleed; Livingston, Gill; Sommerlad, Andrew; Oomman, Sabu; et al. (Lancet, 2018)
Background